Improvements in muscular endurance following a baseball specific strengthening program in high school baseball players - Moore, S. D.; Uhl, T. L.; Haegele, L. E.; Kibler, W. B. (Journal of Athletic Training, 2012)
Context: Preventative strengthening programs for adolescent baseball players have been suggested, but little empirical data exist regarding their effectiveness for this population. Objective: To determine changes in upper extremity muscular endurance in adolescent baseball players during an 8 week pre-season training regimen with follow up at 20 weeks, which represented the start of the spring baseball season. Secondarily, changes in strength, range of motion and inseason time lost to injury were examined. Design: Pre-test post-test. Setting: Sports medicine clinic. Participants: 14 baseball players (age=16±2yr; ht=182±8cm; mass= 75±11kg; 11 pitchers/catchers) with no recent injury were tested at 4, 8 and 20 weeks. Interventions: Participants attended three supervised training sessions/week. Strengthening of the scapular, rotator cuff and forearm muscles was performed using a stairstep progression emphasizing repetition over load. Additional conditioning for the lower extremity (LE) was imple-mented for major muscle groups using body weight and elastic resistance. Main Outcome Measures: Internal rotation (IR) and external rotation (ER) strength and motion were assessed at 90° abduction. Posterior shoulder endurance test (PSET), measured in Nm, required the participant to perform repetitions to failure of prone horizontal abduction to 90° using 2% of their body. PSET reliability was performed a priori (ICC=.81, SEM=13.7Nm). Maximum distance hopped on a single leg was used to evaluate LE strength. Separate mixed model linear analyses were performed for each variable, followed by a Bonferroni post-hoc analysis as appropriate (a<.05). Results: Posterior shoulder endurance improved (p<.001), increasing from 437±209Nm at baseline to 941±472Nm at 4 weeks (p=.001) and remained elevated throughout the program. Single leg hop work improved bilaterally (p<.001), increasing from 1006±278Nm to 1505±354Nm in the lead leg and from 959±271Nm to 1451±362Nm in the stance leg at 4 weeks (p<.001) and remained elevated throughout the program. IR ROM, total arc of motion (ER+IR) and ER/IR strength ratio did not change over the course of the program (p>.05). For the 13 participants who played spring baseball, the total player-games for the 10 week season equaled 270 exposures. Three participants sustained injury during the season (sprained ankle, back muscle strain, hamstring strain), for a total of 7 games missed due to injury. No shoulder or elbow injuries were reported. Conclusions: While muscular endurance increased, strength did not, which reflects the specificity of training of this program toward endurance and is likely due to the preexisting high strength ratio in this cohort. These findings indicate clinicians should address both strength and endurance as separate constructs. Assessment and training of endurance is of particular importance given the documented link between arm fatigue and shoulder pain in throwers. This study describes a simple clinical measurement of shoulder endurance. Finally, this evidence suggests that participants in the pre-season training program were adequately prepared for the season and incurred minimal time loss due to injury.